The impact of adolescents’ voice through an online school radio: a socio-emotional learning experimental project - Sarmento, Patrícia; Lobo, Mafalda; Kirtikumar, Kalpna (Frontiers in Psychology, 2024)
Universal school-based socio-emotional learning (SEL) programs for adolescents have shown their efficacy in producing positive outcomes. The aim of the current study is to present an original school-based program and project for adolescents - Semear Valores On-air – and to assess the relationship between participation in the project and students’ socio-emotional skills. Based on the character strengths and virtues model, this online school radio project aimed at promoting communication, creative thinking, adaptability, and resilience skills in adolescents and giving them the opportunity to become influential agents of well-being and citizenship. As part of the school curriculum, students were invited to create and record radio shows and podcasts. An online school radio was thus created, and it continues to broadcast all over the world, with music, daily shows, and interviews 24/7. It was developed within the framework of the Gulbenkian Academies for Knowledge, a nationwide Portuguese program, that seeks to prepare children and youth for change, to enable them to deal with complex problems, and to expand their opportunities for achievement. A quasi-experimental design, with a mixed qualitative-quantitative approach was used to analyze data collected from 112 adolescents in the second year of its implementation, in 2020-2021. Results suggest that 1) teachers’ perceptions of student’s socio-emotional skills in the post test showed more positive associations with the participation in the project, than participant’s perceptions; 2) students identified eight types of lessons learned, the one most referred was the improvement of socio-emotional skills and learning about themselves; and 3) the combined opportunities for adolescents to learn more about themselves, to express themselves and to practice socio-emotional skills are important ingredients for their motivation and active engagement in the project. Overall, these results indicate that participation in the project is associated with positive outcomes for the adolescents and that both monitoring and evaluation data are very important to interpret the outcomes in a more comprehensive manner.